PENGARUH KECUKUPAN ASUPAN ASI TERHADAP RISIKO TERJADINYA IKTERUS NEONATORUM DI YOGYAKARTA - , Ida Nursanti; , Prof. dr. Djaswadi Dasuki, SpOG(K)., ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Neonatal jaundice (icterus neonatorum) is a common problem in infants in the first week after birth. Sixty percents of healthy infants born full term are at risk of neonatal jaundice and 5-12% of breastfed infants are at risk of developing severe jaundice. Bilirubin encephalopathy causes severe jaundice/kernicterus and the baby suffering from kernicterus will experience impaired growth and development. Kernicterus can be prevented with optimal management of breastfeeding. Adequacy of breast milk ensures adequate intake of calories and fluid and reduce the risk of neonatal jaundice in infants. Utilization of sunlight is also common done by people to overcome neonatal jaundice in infants. Objective: To reduce the risk of neonatal jaundice in Yogyakarta